Expert Consensus of Clinical Diagnosis and Treatment of Traumatic Spinal Cord Incomplete Injury in Traditional Chinese Medicine - Chiropractic Section of China Association of Chinese Medicine; Li (Writed by) LI; Jun (Writed by) LENG; Xia (Writed by) ZHOU (康复学报)
Trauma is the primary cause of spinal cord injury. Based on evidence-based medicine, Expert Consensus of Clinical Diagnosis and Treatment of Traumatic Spinal Cord Incomplete Injury in Traditional Chinese Medicine(TCM) is need to standardize the TCM clinical diagnosis and treatment technology, to improve clinical efficacy. The expert consensus provides the characteristics of Chinese medicine ridge rectification, the syndrome differentiation and treatment. The expert consensus is based on the principles of evidence-based medicine and the classification criteria of TCM literature, and compiled according to the rules of clinical diagnosis and treatment guidelines in combination with expert demonstration, peer consultation and clinical evaluation. The process was standardized in terms of scope, terminology and definition, the diagnosis, differentiation of symptoms and signs, treatment, and efficacy criteria, so as to provide guidance and reference for clinicians of chiropractic, rehabilitation and orthopaedics of TCM. In the treatment part of the expert consensus, the principle, non-drug treatment, drug treatment and matters needing attention are put forward.